Pesquisa dos agentes infecciosos causadores da toxoplasmose, linfadenite caseosa e maedi-visna em ovinos - Moura, Gabriela Hémylin Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
Infectious contagious diseases such as Toxoplasmosis, Casein Lymphadenitis and Maedi-visna can cause coinfections aggravating animals’ health. Toxoplasmosis is a zoonosis that causes reproductive losses in sheep. Caseous lymphadenitis is a disease that presents in a chronic and debilitating way. Maedi-visna is a multisystemic infection with chronic evolution and inapparent signs. Due to the importance of these diseases and their possible co-infections in sheep, the objective was to investigate the infectious agents that cause diseases in sheep in the municipality of Limoeiro do Norte-CE. The totality of 402 samples of undefined sheep belonging to 20 farms was collected in an extensive manner, of different ages and sex. For the diagnosis of diseases, Casein Lymphadenitis and Toxoplasmosis, the ELISA immunoenzymatic assay was used and for Maedi-visna the agar gel immunodiffusion technique (AGID). It is concluded that Lymphadenitis Caseosa is present in the region with the highest prevalence in the matrices 42,53% (94/221), positive sheep for Toxoplasmosis were also found 14,09% (34/228), but no statistically significant difference variables, while the sera analyzed for Maedi-visna were negative. And in relation to coinfections the category of the breeders were the most affected with 19.04% (4/21). It is concluded that researches increase the knowledge regarding the diseases of that region and facilitates the execution of the prophylaxis measures
Keywords: zoonose; coinfecção; ovino; zoonosis; coinfection; ovine; CIENCIAS AGRARIAS::MEDICINA VETERINARIA